Thoracic ultrasound combined with low-dose computed tomography may represent useful screening strategy in highly exposed population in the industrial city of Taranto (Italy) - Quarato, Carla Maria Irene; Dama, Elisa; Maggi, Michele; Feragalli, Beatrice; Borelli, Cristina; Del Colle, Anna; Taurchini, Marco; Maiello, Evaristo; De Cosmo, Salvatore; Lacedonia, Donato; Barbaro, Maria Pia Foschino; Carpagnano, Giovanna Elisiana; et al. (Frontiers in Medicine, 2023)
Objectives. We validated a screening protocol in which thoracic ultrasound (TUS) acts as a first-line complementary imaging technique in selecting patients which may deserve a second-line HRCT scan among a population of asymptomatic high-risk subjects for interstitial lung disease (ILA) and lung cancer. Due to heavy environmental pollution burden, the district Tamburi of Taranto has been chosen as “case study” for this purpose. Methods. From July 2018 to October 2020, 677 patients who have been living in Tamburi for at least 10 years were included in the study. A total of 167 subjects agreed to undergo both a TUS examination and a second-line high-resolution computed tomography (HRCT) scan. Results. TUS showed an overall sensitivity of 95.3% and specificity of 81.7% in detecting pleuro-pulmonary alterations in comparison with HRCT scan. Presence of suspicious sonographic features on ultrasound showed a high positive predictive value (84.4; 95% CI: 77.1-91.6) for actual pleuro-pulmonary disease. Absence of suspicious sonographic features had a high negative predictive value (94.4; 95% CI: 89.0-99.7). When the evaluation matched a specific pulmonary alteration (i.e., fibrotic changes or pulmonary nodules) with determinate sonographic findings, a reduction in both TUS sensibility and specificity was recorded. The combined employment of TUS examination and HRCT scans scored 34 cases with early subpleural ILA and diagnosed 3 patients with lung cancers. Conclusions. A first-line TUS examination stratified high-risk subjects in an exposed population which were eligible to a second-line low-dose screening HRCT scan to early diagnose ILA and lung cancer. Protocol registration code: PLEURO-SCREENING-V1.0_15 Feb, 17